RELATIONSHIP BETWEEN ADVERSITY INTELLIGENCE AND CAREER ADAPTABILITY IN STUDENTS OF THE DEPARTMENT OF INDUSTRIAL TECHNOLOGY VOCATIONAL SCHOOL DIPONEGORO UNIVERSITY THIRD YEAR - Rahma Zahidah Pertiwi; Dian Ratna Sawitri (Jurnal EMPATI, 2023)
This study aims to determine the relationship between adversity intelligence and career adaptability in students of the Department of Industrial Technology, Vocational School, Diponegoro University in Semarang, Central Java. The study population was 423 students of the Department of Industrial Technology of the Vocational School of Diponegoro University, and a sample of 204 people were taken using convenience sampling techniques. Measuring instruments used were the Adversity intelligence scale (39 items, α = 0.931) and the Career Adaptability scale (40 items, α = 0.952). Spearman Rank non-parametric correlation analysis shows that there is a significant positive relationship between adversity intelligence and career adaptability in students of the Department of Industrial Technology Vocational School of Diponegoro University, with a correlation coefficient of rxy = 0.702 (p <0.05). The higher adversity intelligence, the higher the career adaptability they have.